Necessary reforms in the Greek academic system - Stamatakis, Alexandros; Tsakalides, Panagiotis; Tamiolaki, Melina (Frontiers in Political Science, 2024)
Motivated by our EU funded ERA chair projects, that require proposing reforms to yield the Greek academic system more competitive with a particular emphasis on fostering brain gain and preventing brain drain, we propose policy changes on a wide range of topics, based on our joint academic management experience inside and outside of Greece in conjunction with our diverse backgrounds in the humanities, computer science, and the life sciences. The proposed reforms can contribute to increase the competitiveness of Greece in research and development (R & D). We classify proposals by their associated costs and include a plethora of zero cost proposals that do have the potential to increase efficiency and net research time as well as to improve current working conditions in Greek academia. However, to yield Greece more competitive at the international level, reverse brain drain, and foster brain gain, substantial investments and increases of R&D expenditure are required which depend on political willingness and require a long term strategic development plan for Greece beyond being a tourist destination in the European periphery.